2023
DOI: 10.1039/d3nj01546g
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of carbon coated hyperdispersed Ru nanoparticles supported on TiO2 HER electrocatalysts by dye-sensitization

Abstract: Hydrogen production by water-splitting is a very promising strategic energy technology and one of the most important means to obtain green hydrogen. It is of great practical significance to develop...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In comparison, the catalytic activity of Ru–C increased significantly, and the overpotential decreased greatly to 50 mV, which is comparable to that of Pt/C. The overpotential of Ru–C is also compared with many reported Ru-based catalysts, such as Ru 0.1 @H-MoS 2 (51 mV), Ru@Co/N-CNTs (48 mV), C/Ru/TiO 2 (51 mV), Ru-CoP (47 mV), Ru–Cu­(OH) x /CF (45 mV), and Ru/NSC-200 (50 mV) (Figure b and Table S1 for details). It can be seen that Ru–C is very advantageous as an HER catalyst.…”
Section: Resultsmentioning
confidence: 75%
“…In comparison, the catalytic activity of Ru–C increased significantly, and the overpotential decreased greatly to 50 mV, which is comparable to that of Pt/C. The overpotential of Ru–C is also compared with many reported Ru-based catalysts, such as Ru 0.1 @H-MoS 2 (51 mV), Ru@Co/N-CNTs (48 mV), C/Ru/TiO 2 (51 mV), Ru-CoP (47 mV), Ru–Cu­(OH) x /CF (45 mV), and Ru/NSC-200 (50 mV) (Figure b and Table S1 for details). It can be seen that Ru–C is very advantageous as an HER catalyst.…”
Section: Resultsmentioning
confidence: 75%
“…The Tafel slope is an important indicator of the kinetic behaviour of the catalysts—the lower the value, the faster the reaction kinetics. 37 The Tafel slope for hcp RuIn NPs/C also showed that the rate-determining step of the HER is the Tafel step. 38 The hcp RuIn NPs/C also exhibited the highest mass activity (47.98 and 177.78 A g −1 for η 10 and η 20 , respectively), compared with commercial Pt NPs/C (24.48 and 83.02 A g −1 for η 10 and η 20 , respectively), fcc RuIn NPs/C (24.18 and 96.08 A g −1 for η 10 and η 20 , respectively) and hcp Ru NPs/C (15.48 and 38.08 A g −1 for η 10 and η 20 , respectively), as shown in Fig.…”
mentioning
confidence: 98%